Aspectos biológicos del calamar patagónico Loligo gahi (Cephalopodo: Loliginidae) en Huarmey, Perú - Cardoso, Franz (1998)
Loligo gahi Orbigny, Patagonian squid, biology was studied in base to samples from artisanal fishery catches between February and March of 1985 in Huarmey, Perú. Characteristics of population structures, reproduction and feeding were analyzed.